2015
DOI: 10.1111/mve.12096
|View full text |Cite
|
Sign up to set email alerts
|

Divergent host preferences of above‐ and below‐ground Culex pipiens mosquitoes and their hybrid offspring

Abstract: Culex pipiens form pipiens and Cx. pipiens form molestus (Diptera: Culicidae) belong to a cosmopolitan taxonomic group known as the Pipiens Assemblage. Hybridization between these forms is thought to contribute to human transmission of West Nile virus (WNV) in North America. Complementary choice and no-choice landing assays were developed to examine host acceptance by North American Cx. pipiens in the laboratory. Populations collected from above- and below-ground sites in suburban Chicago were identified as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 46 publications
2
85
0
Order By: Relevance
“…A recently published study suggested that hybrid offsprings between the pipiens and molestus forms are an important for epizootic transmission of WNV in North America [66]. During the 2012 outbreak in Croatia, mosquitoes were sampled within the area of appearance of WNV neuroinvasive human cases in three north-eastern counties.…”
Section: Culex Pipiensmentioning
confidence: 99%
“…A recently published study suggested that hybrid offsprings between the pipiens and molestus forms are an important for epizootic transmission of WNV in North America [66]. During the 2012 outbreak in Croatia, mosquitoes were sampled within the area of appearance of WNV neuroinvasive human cases in three north-eastern counties.…”
Section: Culex Pipiensmentioning
confidence: 99%
“…These laboratory findings are supported by field studies carried out in northern Europe, which reported serological evidence of WNV in sentinel chickens, resident birds, and migratory birds in the United Kingdom (Buckley et al 2006, Buckley et al 2003, and in migratory birds in Germany (Linke et al 2007). This evidence may suggest that WNV is already circulating among birds Introduction 1 they have a relatively high infection prevalence in the field (Engler et al 2013, Hayes et al 2005, strong preference to feed on bird hosts (Fritz et al 2015, Hamer et al 2009, Osório et al 2014, and high abundance during summer (Chaskopoulou et al 2016, Spielman 2001, which together makes Cx. pipiens a potentially important contributor to WNV transmission (Kilpatrick et al 2005).…”
Section: Vertebrate Hosts Of West Nile Virusmentioning
confidence: 99%
“…The two biotypes can hybridize, and hybrids show intermediate behaviour. Due to their more opportunistic feeding behaviour, hybrids are considered important bridge vectors which can transmit WNV from birds to humans (Fritz et al 2015, Kilpatrick et al 2005. Behavioural differences between biotypes may have implications for their contribution to the WNV transmission cycle.…”
Section: Vertebrate Hosts Of West Nile Virusmentioning
confidence: 99%
See 2 more Smart Citations